Small town girls : a writer's memoir - Phillips, Jayne Anne, 1952- (Alfred A. Knopf, 2026)
"Appalachia-a distinctly American landscape, dense with forests and small churches, rich in history and misunderstandings-has been the great setting for Jayne Anne Phillips's work. She grew up in the small town of Buckhannon, West Virginia and has always kept it close, even as she and her boundless imagination have traveled. In these essays, Phillips brings us into her childhood and family, most movingly her mother. She recreates the place she calls home, both its history and its foundational truths. She traces her journey across the country in search of love and work and belonging, and offers insights into the fellow writers and cultural touchstones that helped shape her path. From the local beauty salon to the legendary Hatfield-McCoy feud, from Jean Shrimpton and Barbara Stanwyck to Stephen Crane and Breece D'J Pancake, Jayne Anne ponders her relationship with inspiration, religion, culture, and the troubled annals of the last American centuries. Tender, inviting, sparkling with wisdom and open-heartedness, Small Town Girls is a portrait of an inimitable artist as well as a love letter to the place and the people who have made her who she is"-- Provided by publisher.